PENGARUH PENGENDALIAN INTERNAL COSO TERHADAP KEBERLANGSUNGAN LEMBAGA PERKREDITAN DESA (LPD) - Ni Kadek Irdian Apri Ani; Sagung Oka Pradnyawati; Ni Luh Putu Widhiastuti; Kadek Indah Kusuma Dewi; Ni Kadek Mita Lestari (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
Internal control according to the Committee of Sponsoring Organizations of The Treadway Commission (COSO) in 1992 can be used to establish effective internal controls in an organization including for sustainability Village Credit Intitution (LPD). The object of this research is the city of Denpasar. The stages of the research begin with the identification of issues, collection of theories and hypotheses, observation of the population and samples, data collection, testing phase, analysis and reporting of results. Moderated Regression Analysis and qualitative descriptive analysis were used as analytical tools in this study. The results show that COSO-based internal control has a positive impact on the sustainability of the LPD.